Realitas Ekonomi Sumber Daya Manusia Dalam Upaya Penerapan Digitalisasi Pasar Rakyat di PT. Mikrobisnis Digital Sejahtera - Dita Pratiwi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to describe projects in the Magang dan Studi Independen Bersertifikat or abbreviated as MSIB which are carried out at INAmikro (PT. Mikrobisnis Digital Sejahtera) which was carried out within a span of 5 months starting from February 21 2023 to July 30 2023. This study uses a descriptive analysis method to explain various projects carried out while participating in a internship at PT. Mikrobisnis Digital Sejahtera. This research concludes that the certified apprentice program implemented PT. Mikrobisnis Digital Sejahtera is a project designed to help business people with problems in implementing people's market digitization in the micro and ultra micro business sector. By looking at the various problems faced by business actors, of course, highly trained human resources are needed so that the program is implemented. by PT. Mikrobisnis Digital Sejahtera (INAmikro) can continue and develop. The results of this study are to provide an overview to the reader about how the project was carried out during this internship program.